Pengaruh Penggunaan Digital payment dan Literasi Keuangan Syari'ah Terhadap Perilaku Konsumtif - Ruhliandini, Putri Zafira; Mayanti, Yuni; Kamali, Ahmad Nurkamali; Maharani, Indah Maharani (Jurnal Dimamu, 2025)
The rapid development of financial technology and the massive penetration of digital payment among students raise concerns about the increase in consumptive behavior due to the transaction ease that reduces the "pain of paying". this study aims to analyze the partial and simultaneous effects of digital payment use  and sharia financial literacy on consumptive behavior in FEBI Universitas Ma’soem students. This explanatory quantitative descriptive research utilized 158 respondents selected through purposive sampling. Data analysis was performed using multiple linear regression, t-test, and F-test. The results indicate that, partially, digital payment use has a positive and significant effect on consumptive behavior, establishing it as the primary driving factor. Conversely, sharia financial literacy is partially correlated positively, significantly but weakly—a contradictory finding to sharia ethical principles. In the simultaneous model, although sharia financial literacy shows a negative direction (in line with theory), its influence is not statistically significant. Collectively, digital payment and sharia financial literacy affect consumptive behavior, contributing 39.3% of the observed variation. The main conclusion is that the dominant effect of digital payment cannot be effectively counterbalanced by sharia financial literacy knowledge alone; practical implementation of Sharia ethics is necessary to control student consumptive behavior.